A Novel Secure S-box Design Methodology Based on FPGA and SHA-256 Hash Algorithm for Block Cipher Algorithms - Aydin, Yilmaz; Garipcan, Ali Murat; Ozkaynak, Fatih (Springer Heidelberg, 2025)
In this study, a novel robust design methodology that successfully meets the performance and security criteria for substitution-boxes (s-boxes), critical component in block cipher systems, is proposed. Unlike traditional methods providing low-level randomness, the proposed method utilizes physical true randomness as the entropy source, significantly improving the robustness and effectiveness of the s-box design. Phase noise (jitter) occurring on ring oscillators (ROs) is used for true randomness inputs with high security and unpredictability properties in the proposed method. The success of the proposed method is evaluated by considering key performance metrics of s-boxes such as bijectivity, strict avalanche criterion (SAC), bit independence criterion (BIC), nonlinearity (NL), and differential probability (DP). In the novel method, including the integration of the secure hashing algorithm (SHA)-256 hash function for cryptographic usage adequacy of the noise signal, 106.75 NL, 0.4995 SAC, and 105.7 average BIC-NL values can be obtained for s-boxes without any additional optimization process. Considering the low DP value, the analysis results confirm that the s-boxes produced by the proposed method can provide remarkable resistance against linear and differential cryptanalysis scenarios. Numerical findings also show that the proposed s-boxes are competitive and superior compared to other s-box designs in the literature. In conclusion, we believe that the methodology producing robust and reliable s-box solutions for block cipher systems contains important contributions inspiring future research regarding design principles.
Keywords: Cryptography; S-box; Phase jitter; FPGA; SHA-256